Kød og blod: Arvesyndslæren som selviagttagelsesskema - Pallesen, Carsten (Dansk Teologisk Tidsskrift, 2024)
This article discusses the doctrine of ‘hereditary sin’ as the theological context of baptism in article 2 of the Lutheran Confessio Augustana (1530). Since the Danish constitution supports the “Evangelical-Lutheran church”, the theological, judicial and political interpretation of this article is an issue of controversy. Niklas Luhmann’s theory of functional differentiation of social systems offers a clue for a clarification. On Luhmann’s account, the dogma of hereditary sin, which was formulated by Augustine in the early Latin church, is a deliberate uncoupling of religion from the family: The forefathers are no longer the object of worship, since they like all men are sinners to be prayed for, rather than prayed to. In a contemporary perspective, the doctrine of hereditary sin offers an unprecedented “schematism of self-observation” which Paul Ricœur’s hermeneutics of religious symbols qualifies. These hermeneutical and sociological perspectives should be taken into consideration in the debate over the Lutheran heritage in the Danish religious and political context.